THE INFLUENCE OF ACTIVITIES CUT THE GRASS ON THE FINE MOTOR SKILLS OF CHILDREN AGED 4-5 YEARS AT PAUD BUNGONG JEUMPA PIDIE JAYA - Lina Amelia; Faizatul Faridy; Putri Shafina (Bunayya, 2023)
The way a child can use his finger skills to reach, grasp, release, clench, and hold an object well is included in fine motor skills. Based on observations at PAUD Bungong Jeumpa Pidie Jaya, it was found that 9 out of 17 children in Kindergarten A aged 4-5 years showed that their fine motor development was not yet optimal, thus disrupting the learning process, such as children having difficulty cutting, drawing lines on paper and appearing clumsy using tools. writing tools. This research aimed to determine the influence of Cut the Grass activities on fine motor skills in children aged 4-5 years at PAUD Bungong Jeumpa Pidie Jaya. The quantitative research method used a pre-experimental approach using one group pretest-posttest design with a total sampling technique, and the instruments used were observation and documentation sheets with 17 children as samples. In hypothesis testing using the tcount and ttable tests, the value of tcount > ttable was obtained, namely 11.57 > 1.74588, namely rejection of Ho and acceptance of Ha, meaning that there is an influence of the cut the grass activity on the fine motor skills of children aged 4-5 years at PAUD Bungong Jeumpa Pidie Jaya